A case study of animated book covers for promoting publishers in Malaysia - Abdul Rahim, Nur Afifah; Hairul Anuar, Inda Murni; Che Din, Sharkawi; Mohd Lazim, Nur Aniza (Universiti Teknologi MARA, Perak, 2025)
The evolution of new technology is changing the consumer perspective of Malaysia’s audience, including the book industry. More digital bookstores are popping up, while physical stores are declining as preferences change along with the evolution of technology. This study examines the components used in designing animated book covers, using a content analysis of ten (10) samples of digitally illustrated book covers from several publications. The aim is to understand the components of book cover design and how motion was implemented in the animated book cover. The findings showed that the most common element of book covers to be animated is cover art illustration. Results revealed the pattern of visual components animated in book cover design and suggested guidelines to aid publishers in Malaysia.